2019
DOI: 10.3390/diagnostics9040153
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of Point-of-Care Ultrasound Implementation in Resource-Limited Settings

Abstract: Background: Nearly half of the world lacks access to diagnostic imaging. Point of care ultrasound (POCUS) is a versatile and relatively affordable imaging modality that offers promise as a means of bridging the radiology gap and improving care in low resource settings. Methods: We performed semi-structured interviews of key stakeholders at two diverse hospitals where POCUS implementation programs had recently been conducted: one in a rural private hospital in Haiti and the other in a public referral hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Our findings were similar to prior qualitative research on the implementation of point-of-care ultrasound and more broadly, point-of-care diagnostics in LMIC. 30–32 Key stakeholder perspectives revealed that training as well as cost and maintenance of materials were major barriers to use, while improved diagnostic accuracy, timely diagnosis and portability were major benefits. 30–32 When considering point-of-care diagnostics more broadly, stakeholders emphasised cost-effectiveness evaluations and improving quality management systems, again supporting the importance of cost containment and quality of healthcare delivery through trained staff and functional equipment for sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to prior qualitative research on the implementation of point-of-care ultrasound and more broadly, point-of-care diagnostics in LMIC. 30–32 Key stakeholder perspectives revealed that training as well as cost and maintenance of materials were major barriers to use, while improved diagnostic accuracy, timely diagnosis and portability were major benefits. 30–32 When considering point-of-care diagnostics more broadly, stakeholders emphasised cost-effectiveness evaluations and improving quality management systems, again supporting the importance of cost containment and quality of healthcare delivery through trained staff and functional equipment for sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Key stakeholder perspectives revealed that training as well as cost and maintenance of materials were major barriers to use, while improved diagnostic accuracy, timely diagnosis and portability were major benefits. [30][31][32] When Open access considering point-of-care diagnostics more broadly, stakeholders emphasised cost-effectiveness evaluations and improving quality management systems, again supporting the importance of cost containment and quality of healthcare delivery through trained staff and functional equipment for sustainability. 31 Acceptance and adoption of new technology Quality control and device functionality ensure that the building blocks for successful implementation are in place and can be sustained over time.…”
Section: Device Maintenance and Functionalitymentioning
confidence: 99%
“…The semi-structured interview guide was designed to explore hospitalists’ perceptions and attitudes toward current tools available to evaluate for volume status, parameters to determine discharge-readiness, utility of lung ultrasound and the factors that influence its adoption (see Supplementary Material). All interviews were conducted by a physician with prior experience with qualitative interviews[16] (AMM).…”
Section: Methodsmentioning
confidence: 99%
“…The semi-structured interview guide was designed to explore hospitalists' perceptions and attitudes toward current tools available to evaluate for volume status, parameters to determine discharge-readiness, utility of lung ultrasound and the factors that influence its adoption (see Appendix). All interviews were conducted by a physician with prior experience with qualitative interviews (AM) [16].…”
Section: Data Collectionmentioning
confidence: 99%